PENGARUH PEMUTIHAN PAJAK KENDARAAN BERMOTOR, SOSIALISASI PAJAK, DAN KUALITAS PELAYANAN PAJAK TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR DI JAKARTA TIMUR - Fitrianti, Sabrina; Musyaffi, Ayatulloh Michael; Nindito, Marsellisa (LPPM Universitas Bina Bangsa, 2023)
The purpose of this study is to determine whether or not there is an influence of motor vehicle tax bleaching, tax socialisation, and tax service quality on the compliance of motor vehicle taxpayers in East Jakarta. The population in this study is motor vehicle taxpayers who are registered at the Jakarta SAMSAT office, a total of 1,165,460. The number of samples used was 137 respondents. The sampling technique used is probability sampling using simple random sampling method measured by a Likert scale of 1-5. The type of research used was quantitative using multiple linear regression analysis and processed using the SPSS version 29 program. The results of the F statistical test indicated that motor vehicle tax bleaching (X1), tax socialisation (X2) and quality of tax services (X3) had a simultaneous effect (together) on motor vehicle taxpayer compliance (Y). The results of the hypothesis test (T-test) on each variable X to Y stated that: Car tax bleaching, tax socialisation and quality of tax services have a positive effect on car tax compliance